DC MOTOR SPEED CONTROL - Iyad Ali; Saleh Dragmeh (My University, 2009)
Permanent Magnet   DC motors are increasingly being used in a wide spectrum of applications such as domestic equipments, automobiles, information technology equipment, industries, public life appliances.. Direct current (DC) motors comprise one of the most common types of actuator designed into electromechanical systems. They are a very straightforward and inexpensive means of creating motion or forces.